A microRNA allele that emerged prior to apple domestication may underlie fruit size evolution. (October 2015) - Yao, Jia‐Long; Xu, Juan; Cornille, Amandine; Tomes, Sumathi; Karunairetnam, Sakuntala; Luo, Zhiwei; Bassett, Heather; Whitworth, Claire; Rees‐George, Jonathan; Ranatunga, Chandra; Snirc, Alodie; Crowhurst, Ross; et al.
Summary The molecular genetic mechanisms underlying fruit size remain poorly understood in perennial crops, despite size being an important agronomic trait. Here we show that the expression level of a microRNA gene (miRNA172) influences fruit size in apple. A transposon insertional allele of miRNA172 showing reduced expression associates with large fruit in an apple breeding population, whereas over‐expression of miRNA172 in transgenic apple significantly reduces fruit size. The transposon insertional allele was found to be co‐located with a major fruit size quantitative trait locus, fixed in cultivated apples and their wild progenitor species with relatively large fruit. This finding supports the view that the selection for large size in apple fruit was initiated prior to apple domestication, likely by large mammals, before being subsequently strengthened by humans, and also helps to explain why signatures of genetic bottlenecks and selective sweeps are normally weaker in perennial crops than in annual crops.